The Principle of Pacta Sunt Servanda in Fintech Transactions is Reviewed Through The Perspective of Ushul Fiqh - Septarina Budiwati; Muhammed Junaidi; Wisnu Tri Nugroho (AL- IKTISAB Journal of Islamic Economic Law, 2020)
The principle of Pacta Sunt Servanda as part of the legal principle, which is commonly described as "agreement as applicable to the author" carries its own implications in the practice of society, where the public must perform the agreement consistently, consequent, and full of responsibility. No exception in transactions in Financial Technology (Fintech), the applicability of this principle to be a reference for both parties to equally believe that the transaction process (lending) between them can be held accountable in terms of moral-ethical laws. The purpose of this research is to describe the validity of the pacta sunt servanda of the agreement on Fintech and describe the pacta sunt servanda basis reviewed through the study of ushul fiqh to soften a concrete solution against legal problematics that exist on Fintech. The methods used in this study are juridical-normative.The results of the research show that with the trend of ease carried by the Fintech can erode the essence of the principle of the law itself, and create a destructive mindset which is an agreement of the regarded as administrative terms that need to be met when conducting transactions on Fintech, so that various provisions inherent to the unreached Fintech agreements. In addition to the absence of strict supervision in the process of Fintech transactions facilitate the occurrence of fraud against the initial purpose of granting Fintech funds by the loan recipients.